Linguistic Bibliography for the Year 2002 and Supplement for previous years - Шмігер, Т. (Мовознавство, 2010)
Відгук на зведену бібліографію європейської мовозначної літератури:
LINGUISTIC BIBLIOGRAPHY FOR THE YEAR 2002 AND SUPPLEMENT FOR PREVIOUS YEARS / Ed. by S. Tol and H. Olbertz with the assistance of P. van Beest and Th. Horstman.— Dordrecht, Springer, 2006.— CVIII, 1445 p.— (Permanent International Committee of Linguists).

LINGUISTIC BIBLIOGRAPHY FOR THE YEAR 2003 AND SUPPLEMENT FOR PREVIOUS YEARS / Ed. by S. Tol and H. Olbertz with the assistance of D. Glandorf and Th. Horstman. — Dordrecht, Springer, 2007.— CVI, 1161 p.— (Permanent International Committee of Linguists).